Information literacy : a practitioner's guide - Andretta, Susie (Chandos information professional series., 2005)
Taking an international approach, this book explores two main models of Information Literacy or IL: the SCONUL (Society of College, National and University Libraries) Seven Pillars of Information Skills and the IL competencies identified by the ALA (American Library Association). Practical examples for the development of IL skills identified by these models are illustrated using printed and web-based resources. The process of integrating IL provision within a programme of study is outlined to illustrate two strategies underpinning this integration at generic-skills level, the "plug & play" approach, and at subject-specific level, the "research skills approach". A range of diagnostic and assessment methods, to monitor the iterative process of IL skills development, are also presented within these frameworks. -- Publisher description from http://www.woodheadpublishing.com (Oct. 26, 2011)